FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN ALEXO JASTIP DALAM BELANJA ONLINE DI KABUPATEN SIKKA - Bertholomeus Febrayo Lebao; I Gusti Ngurah Satria Wijaya; I Nyoman Bagus Paramartha (JUIMA : JURNAL ILMU MANAJEMEN, 2026)
The development of e-commerce in Indonesia provides convenience while presenting challenges for consumers in regions with limited logistics infrastructure, including Sikka Regency, East Nusa Tenggara, where high shipping costs and restricted product access persist. This condition encourages the emergence of alternative services such as personal shopping assistance (jastip), including AleXo Jastip, which facilitates item consolidation from Surabaya to Maumere. This study aims to identify and understand the factors influencing consumers’ decisions to choose AleXo Jastip amid the availability of similar services. A qualitative phenomenological approach was employed, involving six purposively selected informants with varying backgrounds, professions, and online shopping experiences. Data were collected through in-depth interviews and analyzed using Interpretative Phenomenological Analysis (IPA). The findings reveal that consumer decisions are shaped by structural–economic factors (cost efficiency and limited local market availability), relational–social factors (trust, social ties, and concern for item safety), and emotional–experiential factors (professionalism, comfort, and satisfaction). AleXo Jastip is perceived as a service partner that offers economic value, security, and social connectedness. The study concludes that strengthening trust-building mechanisms, service interaction quality, and consistency is essential. Recommendations include developing a more structured ordering system, enhancing service transparency, and exploring loyalty strategies to improve competitiveness in regions with logistical constraints.